Odpowiedzi

2010-03-27T18:42:17+01:00
A)
4/5y=1
y = 1 : 4/5
y= 1 * 5/4
y= 5/4

5/4y=2
y = 2 : 5/4
y = 2* 4/5
y = 8/5

-6/7y=3
-y = 3 : 6/7
-y = 3 * 7/6
-y = 21/6
y = -21/6

-1,2y=4
-y = 4 :1,2
-y = 4 * 10/12
-y = 40/12

b)
-8y=5
-y = 5/8
y = -5/8

12y=6
y = 6/12
y = 0,5

-3y=7
-y = 7/3
y = -7/3

6y=8
y = 8/6

c)
-5/6y=1
-y = 1 : 5/6
-y = 1* 6/5
y = -6/5

1/8y=1
y = 1 : 1/8
y = 1*8
y = 8

-1/3y=1
-y = 1: 1/3
-y = 1 * 3
y = -3

9/7y=1
y = 1 : 9/7
y = 1 * 7/9
y = 7/9

Zostawiłam w postaci ułamka niewłaściwego ;)
2010-03-27T18:49:35+01:00
A)
4/5y=1 /: 4/5
y = 1 : 4/5
y = 1 x 5/4
y = 5/4
y = 1 i 1/4


5/4y=2 /: 5/4
y = 2 : 5/4
y = 2 x 4/5
y = 8/5
y = 1 i 3/5


-6/7y=3 / : (-6/7)
y = 3 : (-6/7)
y = 3 x (-7/6)
y = -21/6
y = - 3 i 3/6
y = - 3 i 1/2


-1,2y=4 /: ( -1/2)
y = 4 : (-1/2)
y = 4 x (-2/1)
y = -8

b)-8y=5 / : (-8)
y = 5 : (-8)
y = 5 x (-1/8)
y = -5/8


12y=6 /: 12
y = 6/12
y = 1/2


-3y=7 /: (-3)
y = -7/3
y = -2 i 1/3

6y=8 /:6
y = 8/6
y = 1 i 2/6
y = 1 i 1/3

c)-5/6y=1 6 / : (-5/6)
y = 16 : (-5/6 )
y = 16 x (-6/5)
y = -96/5
y = -19 i 1/5

1/8y=1 /:1/8
y = 1 x 8/1
y = 8


-1/3y=1 /: (-1/3)
y = 1 : (-1/3)
y = 1 x (-3/1)
y = -3

9/7y=1 /:9/7
y = 1 : 9/7
y = 1 x 7/9
y = 7/9
2010-03-27T18:51:07+01:00